Prevalence, clinical characteristics and morbidity of the Asthma-COPD overlap in a general population sample. (4th May 2018) - Ekerljung, Linda; Mincheva, Roxana; Hagstad, Stig; Bjerg, Anders; Telg, Gunilla; Stratelis, Georgios; Lötvall, Jan
ABSTRACT: Objective : Although asthma and chronic obstructive pulmonary disease (COPD) have been regarded as distinct conditions, emerging literature suggests that overlapping phenotypes, called asthma-COPD overlap (ACO), exists. The aim of this study was to describe prevalence, patient characteristics and morbidity of ACO. Methods : From a cross-sectional population sample, the West Sweden Asthma Study, subjects with suspected asthma, chronic bronchitis or COPD, and a random sample, were invited to clinical examinations. ACO was defined as doctor-diagnosed asthma, or clear clinical signs of asthma at examination, with a FEV1 /FVC < 0.7. Results : Subjects were categorized as ACO (N = 181 ), COPD only (N = 89 ), asthma only (N = 651 ) or healthy (n = 1036 ) based on clinical examinations. Prevalence of ACO was 3.4% in the random sample (N = 1172) and 18.1% among asthmatics (N = 138) in the random sample. Subjects with ACO (mean age 59 years, 54% women) had an age and gender distribution in between asthma only (45 years, 63% women) and COPD only (62 years, 41% women). Ever-smoking was reported by 71%, 48% and 74% in the ACO, asthma only and COPD only groups, respectively. Subjects with ACO had worse lung function (mean FEV1 % of predicted normal 76%) than asthma only (100%) and COPD only (87%) and reported more respiratory symptoms. Also respiratory related emergency visits were more common in ACO compared to asthma only and COPD only, respectively. Conclusions : ACO is present in 3.4% of the population and common among subjects with both asthma and COPD. Subjects with ACO had worse lung function and more symptoms than subjects with asthma or COPD only .